2012
DOI: 10.1177/0884533612462899
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Over‐ and Underfeeding Following the Introduction of a Protocol for Weaning From Parenteral to Enteral Nutrition in the Intensive Care Unit

Abstract: A structured protocol for weaning patients from PN to EN can reduce overfeeding in critically ill patients given nutrition support via a combination of routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Protocols should visibly illustrate feeding adjustments when volume based feeds are utilized. Advancement orders also need to be coordinated with decreases in PN 65 …”
Section: Section 5 Procure Select/prepare Label and Dispense Enmentioning
confidence: 99%
“…Protocols should visibly illustrate feeding adjustments when volume based feeds are utilized. Advancement orders also need to be coordinated with decreases in PN 65 …”
Section: Section 5 Procure Select/prepare Label and Dispense Enmentioning
confidence: 99%
“…Dervan and colleagues used a PN weaning protocol in which PN was decreased by 30 mL/h once EN achieved the same rate and was discontinued when EN reached goal infusion rate. They demonstrated less overfeeding with the protocol than prior to the protocol 27 . During times of prolonged weaning, the PN prescription may require daily adjustments with dextrose, amino acids, ILE, and even electrolytes and fluid.…”
Section: Question 13: For Patients Receiving Pn Which Parameters Shomentioning
confidence: 96%
“…Heidegger et al recently reported a decreased risk of nosocomial infections in patients receiving adequate amounts of nutrition versus those receiving 77% of energy targets 10 . Overfeeding has similarly been linked with negative health outcomes such as azotaemia, 11 increased MV time, 12 and altered hepatic function 13 . Complications have been suggested to develop when patients are provided with more than 110% of energy needs, 13 as a result of the increased metabolic demand associated with excess substrate provision and increased carbon dioxide production 14…”
Section: Introductionmentioning
confidence: 99%